(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
Soeren Keil, Multinational Federalism in Bosnia and Herzegovina, Ashgate Publishing Limited: Farnham, 2013, pp. 219, ISBN-13: 978-1138246881, ISBN-10: 1138246883